Post-activation performance enhancement of countermovement jump after drop jump versus squat jump exercises in elite rhythmic gymnasts - Yang, Chengbo; Shi, Lin; Lu, Yanan; Wu, Hongli; Yu, Dawei (Journal of Sport Science and Medicine, 2024)
Drop jump (DJ) and squat jump (SJ) exercises are commonly used in rhythmic gymnastics training. However, the acute effects of DJ and SJ on countermovement jump (CMJ) performance have not been investigated. This study aimed to verify the post-activation performance enhancement (PAPE) responses induced by DJ and SJ with optimal power load and evaluate the relationship between peak PAPE effects and strength levels. Twenty female rhythmic gymnasts completed the following exercises in a randomized order on three separate days: 6 repetitions of DJs; 6 repetitions of SJs with optimal power load; and no exercise (control condition). Jump height was assessed before (baseline) and at 30 seconds and 3, 6, and 9 minutes after each exercise. DJs significantly improved jump height by 0.8 cm (effect size (ES) = 0.25; P = 0.003) at 30 seconds post-exercise compared with baseline. Jump height significantly decreased by-0.35 cm (ES =-0.14; P = 0.021) at 9 minutes after the control condition. SJs significantly improved jump height by 1.02 cm (ES = 0.36; P = 0.005) at 9 minutes post-exercise compared to the control condition. Jump height and relative back squat one-repetition maximum were positively related after performing DJs (r = 0.63; P = 0.003) and SJs (r = 0.64; P = 0.002). DJ and SJ exercises effectively improved countermovement jump height. DJ improved jump height early, while SJ produced greater potentiation effects later. Athletes with a higher strength level benefited the most from these exercises.